L’enjeu de préservation et de protection du patrimoine culturel en Polynésie française : le rôle de l’oiseau à travers des mythes, dans la culture orale traditionnelle - Anthony Tchékémian (Études Caribéennes)
At the end of the 18th century, before the arrival of Europeans in French Polynesia, traditional culture had a close link with nature, in favour of environmental protection. Through myths, birds had a sacred status, that of god or messenger. Over time, this cultural link has been eroded and traditions tend to disappear, with repercussions on the Polynesian natural and cultural heritage. Since then, French Polynesia, an overseas collectivity, has had its own competence in environmental matters. However, the objective of protecting poultry species in the Polynesian territory goes beyond environmental issues. It is also a question of preserving and protecting intangible cultural heritage, which is related to the place of birds in myths and traditional culture. In the era of globalization, the application of concepts such as heritage and sustainable development is essentially economic or even marketing in nature. However, understanding a territory requires taking into account the domain of the irrational.